Insert Media Studies: The Issue of Cinematography of Dance Posts on SocialMedia. - Arif Eko Suprihono (Sense: Journal of Film and Television Studies, 2021)
ABSTRACTThe presence of digital technology encourages the acceleration of the movement of local cultural globalization towards the cultural of world entities. This paper intends to expose upload of dance activities as a new civilization of digital culture with various complexities of its dialogical transformation. Research locus on Classical dance Yogyakarta style entering digital media culture requires a qualitative approach. Many information is found in YouTube media, and some uploads selected for data represent several other uploads. Inquiry starts with obtaining data on media studies, literature studies, interview instruments, and aesthetic product downloads over a large number of samples of social media uploads. The flow of research management is carried out from problem mapping, data collection of uploaded products, literary data tracing, and narrative data networking from local cultural actors, to finally be analyzed, and information meaning. The Yogyakarta palace's globalization movement is real and apparent through cultural citizenship strategy in YouTube cinematography products. The forms of journalistic aesthetic work of various palace activities reflect the trans-contextualization of ideas, social behaviour, and the paradigm of creativity in the fight to recognize new digital culture entities. This paper shows the essence of media transform for the interaction dance dialectical activities with the new entity of the world to achieve a local culture in the global community. ABSTRAKKehadiran teknologi digital mendorong percepatan pergerakan globalisasi budaya lokal menuju budaya entitas dunia. Artikel ini bermaksud untuk mengekspos unggahan kegiatan menari sebagai peradaban baru budaya digital dengan berbagai kompleksitas transformasi dialogisnya. Penelitian lokus pada tarian klasik gaya Yogyakarta memasuki budaya media digital membutuhkan pendekatan kualitatif. Banyak informasi ditemukan di media YouTube, dan beberapa unggahan yang dipilih untuk data mewakili beberapa unggahan lainnya. Penyelidikan dimulai dengan memperoleh data tentang studi media, studi literatur, instrumen wawancara, dan unduhan produk estetika melalui sejumlah besar sampel unggahan media sosial. Alur pengelolaan penelitian dilakukan mulai dari pemetaan masalah, pengumpulan data produk yang diunggah, penelusuran data sastra, dan penjaringan data naratif dari pelaku budaya setempat, hingga akhirnya dianalisis, dan makna informasi. Gerakan  globalisasi  tari Yogyakarta sebagai objek penelitian dan menunjukkan keunikan produk sinematografi di YouTube. Bentuk karya estetika jurnalistik dari berbagai kegiatan istana mencerminkan transformasi ide, perilaku sosial, dan paradigma kreativitas dalam perjuangan untuk mengenali entitas budaya digital baru. Paper ini ingin menunjukkan esensi  transformasi media untuk kegiatan dialektika tari interaksi dengan entitas baru dunia untuk mencapai komunitas global dari sisi studi media. KeywordsDance studies phenomena; screen dance media studies; cinematography of dance; digital culture; social media YouTube.